2016
DOI: 10.1093/idpl/ipw011
|View full text |Cite
|
Sign up to set email alerts
|

Adequacy of data protection in the USA: myths and facts

Abstract: On 6 October 2015, the European Court of Justice (CJEU) invalidated a decision from 2000, wherein the Commission had granted an exception from the general prohibition regarding transfers of personal data outside the European Economic Area (EEA) (CJEU C-362/14, Schrems v Data Protection Commissioner 6 October 2015). Companies in the EEA were permitted to transfer personal data to US companies that had registered under the US Safe Harbor programme (Commission Decision 2000/520/EC, OJ L 215, 25 August 2000, 7). D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Both models were developed in the US, which allow certain data DOI 10.18502/kss.v8i1.12657 practices not allowed in Europe, e.g. automated processing of personal information [35]. Furthermore, with the General Data Protection Regulation, the European Union has shown that it takes data privacy and security very seriously.…”
Section: Discussionmentioning
confidence: 99%
“…Both models were developed in the US, which allow certain data DOI 10.18502/kss.v8i1.12657 practices not allowed in Europe, e.g. automated processing of personal information [35]. Furthermore, with the General Data Protection Regulation, the European Union has shown that it takes data privacy and security very seriously.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, a growing number of regions or countries have promulgated laws, policies, or regulations to respond to privacy and security issues in data. For example, the European Union issued the General Data Protection Regulation (Voigt & Von, 2017) and the Personal Information Protection Law by China (Determann et al, 2021). As a result, technical solutions for monitoring CEOs' facial fatigue while preserving personal information are urgently needed.…”
Section: Fatigue Monitoringmentioning
confidence: 99%
“…Article 29 Working Party, 2016). However, the European Commission has also decided that data can be transferred to states that are not particularly renowned for their data protection regimes, including Argentina, Israel, Uruguay and New Zealand (European Commission, 2016), having deemed that those states offer an adequate level of protection of data (Determann, 2016). As regards the Privacy Shield, it remains to be seen how the results of the 2016 Presidential election in the United States will impact upon the perceived sufficiency of data protection there.…”
Section: The Right To Data Protection and In An Era Of Big Datamentioning
confidence: 99%